2018
DOI: 10.1002/hbm.24004
|View full text |Cite
|
Sign up to set email alerts
|

Sensorimotor network alterations in children and youth with prenatal alcohol exposure

Abstract: Children with prenatal alcohol exposure (PAE) often have impaired sensorimotor function. While altered brain structure has been noted in sensorimotor areas, the functional brain alterations remain unclear. This study aims to investigate sensorimotor brain networks in children and youth with PAE using resting-state functional magnetic resonance imaging (rs-fMRI). A parcellation-based network analysis was performed to identify brain networks related to hand/lower limb and face/upper limb function in 59 children … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
30
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 24 publications
(34 citation statements)
references
References 110 publications
(137 reference statements)
3
30
1
Order By: Relevance
“…Similarly, functional MRI studies in older children and adolescents continue to demonstrate disruptions in sensorimotor network connectivity after PAE (e.g. Long et al 2018 ). Further, a study using structural MRI, found decreased subcortical gray matter volume in neonates following PAE ( Donald et al 2016b ), while another study found a smaller corpus callosum after heavy PAE ( Jacobson et al 2017 ) that has implications for network integration.…”
Section: Introductionmentioning
confidence: 97%
“…Similarly, functional MRI studies in older children and adolescents continue to demonstrate disruptions in sensorimotor network connectivity after PAE (e.g. Long et al 2018 ). Further, a study using structural MRI, found decreased subcortical gray matter volume in neonates following PAE ( Donald et al 2016b ), while another study found a smaller corpus callosum after heavy PAE ( Jacobson et al 2017 ) that has implications for network integration.…”
Section: Introductionmentioning
confidence: 97%
“…This level of stability is similar to a previous study in older typically-developing children (Vanderwal et al., 2017), which found correlations of functional connectivity matrices between the first and the second half of the data were approximately 0.60 when watching video clips. The high intra-participant stability in the PAE group was unexpected because children with PAE often have behavioral challenges, atypical neurocognitive responses to visual (Green et al., 2013; Paolozza et al., 2014), auditory (Stephen et al., 2012), and emotional stimuli (Petrenko et al., 2017), as well as altered functional connectivity among brain regions (Donald et al., 2016; Fan et al., 2017; Little et al., 2018; Long et al., 2018). It may be that movie viewing, as opposed to behavioral tasks, moderates the intra-individual variability in children with PAE and leads to higher stability.…”
Section: Discussionmentioning
confidence: 99%
“…Previous resting-state fMRI studies in PAE instructed participants to close their eyes, or acquired data during natural sleep in infants, and found significant between-group differences in functional connectivity compared to unexposed controls (Donald et al., 2016; Little et al., 2018; Long et al., 2018; Wozniak et al., 2013; Wozniak, 2011). It is possible that the passive viewing status here, with its relatively high intra-individual stability, may be less taxing on the brain and thus may not show differences evident in more difficult cognitive tasks.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations